ANALYSIS OF MATHEMATIC REPRESENTATION ABILITY IN CLASS V PRIMARY SCHOOL KPK MATERIAL - Novianti, Novianti; Andriani, Noval (PT Altin Riset Publishing, 2023)
Representation in mathematics is the expression of ideas through models for solving problems in mathematics. These models can consist of words, pictures, diagrams, and shape representations that others can use to finish problems in mathematics. However, it's very unfortunate that representation mathematics is very little understood by most student-based schools. In the KPK material, in the form question story, students involve various form representation mathematics in the finish question. The purpose of this study is to analyze the ability representation mathematics possessed by students in class V/D UPTD SD Negeri 3 Pilot Corruption of KPK material. The method used is qualitative with a shorthand description. Instruments used form a question, essay, or test. The study's findings indicate that students are underrepresented. This will be marked by a completion search for KPK in the tree factors and still not enough ability in verbal representation.